Internet Addiction And Family Relationship In Adolescents: A Cross Sectional Study From Bangladesh - Ara Shampa, Shamima Gulshan; Arjumand, Farzana; Mahjabin, Afsana; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2024)
Background: Internet Addiction (IA) undermine personal relationship when internet replace friends and family. But internet strengthen ties because it makes communication simpler. The aim of this study was to assess the association between IA and family relationship among adolescents. Methods: This cross sectional study was carried out among 203 adolescents (15-19 years) irrespective of their sex who used Internet. The study was conducted at two selected schools in Dhaka city over the period of one year from January to December 2017. Respondents were selected by systematic random sampling; data were collected by face-to-face interview with a semi-structured questionnaire to observe socio-demographic characteristics, scale of Young’s Diagnostic Questionnaire (YDQ) for Internet addiction and Index of family relations (IFR) for family relationship. Data were analyzed by IBM software- SPSS 23 version. Ethical issues were maintained strictly. Results: The study revealed that 34.5% participants were addicted to Internet. Association between sex and internet addiction was found statistically significant (p< 0.01). Restriction by family (p <0.01) and acceptance of physical or mental torture by family members due to internet use (p<0.01) was significantly associated with IA. Among the apps, Facebook (p<0.01) and Instagram (p<0.05) use was significantly associated with IA. Among the purposes, entertainment (p<0.05), making new friends (p<0.01), communication with friends (p<0.05), playing games (p<0.05) and use of Internet by the influence of other family members (p<0.01) were significantly associated with IA. Study revealed that, IA was significantly associated with family relationship. (p<0.01). Conclusion: Findings of this study revealed that IA was associated with family relationship. Effective measures such as: engaging adolescents in outdoor sports, book reading and encouraging them to flourish their hobby can solve the problem of internet addiction. JOPSOM 2021; 41(2):1-11